Analisis Unsur Meluas dan Sistematis dalam Kejahatan terhadap Kemanusiaan Berdasarkan Pasal 7 Statuta Roma - Yulia Tri Wahyuni; Dwi Putri Lestarika (Lembaga Yasin AlSys, 2026)
Crimes against humanity constitute one of the most serious forms of violations of international law because they attack human dignity and the principle of protection for civilian populations. This study aimed to analyze the contextual element of “widespread or systematic” in crimes against humanity under Article 7 of the 1998 Rome Statute and its evidentiary standards in the judicial practice of the International Criminal Court (ICC). This study used a normative juridical method with a qualitative approach through the examination of doctrine, jurisprudence, and relevant international legal documents. The results showed that the element of “widespread or systematic” is a central contextual element that distinguishes crimes against humanity from ordinary criminal offenses. The “widespread” element relates to the scale and impact of attacks against many victims or a broad area, whereas the “systematic” element emphasizes the existence of an organized, planned, and coordinated pattern of conduct. In practice, the ICC assesses this element through quantitative evidence concerning the number of victims, qualitative evidence regarding patterns of planning and logistical coordination, and contextual assessment of the state policy or organization of the perpetrators. These findings also confirm the relationship between crimes against humanity and command responsibility, particularly in assessing the liability of planners or leaders for the acts of their subordinates. The conclusion of this study indicates that proving the element of “widespread or systematic” requires a combination of quantitative, qualitative, and contextual evidence so that only acts that meet the criteria of crimes against humanity can be prosecuted under international criminal law. The implications of this study emphasize the importance of contextual elements in strengthening legal protection for civilian populations and upholding the principles of individual and command accountability.